(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
The perovekites and its derivates like Ruddlesden-Popper series of the general formula An+1BnO3n+1, have a lot of important properties such as electrical, magnetic, and optical properties, alongside its cationic acumination flexibility in both A and B sites, therefor substituting capability which leads to physical properties modifications, hence, developing novel properties, in the light of the above mentioned, in this research we have synthesized the compound Sr2PbO4 which crystallizes in Orthorhombic structure via coprecipitation route for the first time, and the compound Sr2Pb0.75Bi0.25O4 by partial substation of lead with bismuth in x=0.25 ratio. By studying the XRD Patterns it was concluded that the compounds crystallize in Orthorhombic structure (space group Pbam) after the substation was made, a minor reduction in a and c cell parameters were noticed, and by that observation we concluded that the majority of bismuth is in the 5+ oxidation state, the electrical properties were studied using LCR meter by altering the current between the two plates in the range -0.5 - + 0.5 by measuring the current at 1kHz frequency, and by the structure study conclusion of 5+ oxidation state of bismuth therefor the excess electrons will participate in the conduction bond.